A molecular beam/surface spectroscopy apparatus for the study of reactions on complex model catalysts - Libuda, Jörg; et al. (Review of Scientific Instruments, 2000)
We describe a newly developed ultrahigh vacuum (UHV) experiment which combines molecular beam techniques and in situ surface spectroscopy. It has been specifically designed to study the reaction kinetics and dynamics on complex model catalysts. The UHV system contains: (a) a preparation compartment providing the experimental techniques which are required to prepare and characterize single-crystal based model catalysts such as ordered oxide surfaces or oxide supported metal particles; and (b) the actual scattering chamber, where up to three molecular beams can be crossed on the sample surface. Two beams are produced by newly developed differentially pumped sources based on multichannel arrays. The latter are capable of providing high intensity and purity beams and can be modulated by means of a vacuum-motor driven and computer-controlled chopper. The third beam is generated in a continuous or pulsed supersonic expansion and is modulated via a variable duty-cycle chopper. Angular and time-resolved measurements of desorbing and scattered molecules are performed with a rotatable doubly differentially pumped quadrupole mass spectrometer with a liquid-nitrogen cooled ionizer housing. Time-resolved but angle-integrated measurements are realized with a second nondifferentially pumped quadrupole mass spectrometer. In situ measurements of adsorbed species under reaction conditions are performed by means of an adapted vacuum Fourier transform infrared spectrometer. The spectrometer provides the possibility of time-resolved measurements and can be synchronized with any of the beam sources. This contribution provides a general overview of the system and a description of all new components and their interplay. We also present test data for all components employing simple adsorption/desorption and reaction systems. (C) 2000 American Institute of Physics. [S0034-6748(00)04011-9].